Parent-Infant Psychotherapy and Postpartum Depression: The Fathers Participation - Milena da Rosa Silva; Luiz Carlos Prado; Cesar Augusto Piccinini (Paidéia (Ribeirão Preto), 2013)
Given the specificities of postpartum maternal depression, the literature recommends that fathers become involved in psychological interventions within this context. This study presents an investigation of the participation of fathers in parent-infant psychotherapy in the context of maternal postpartum depression. Two families participated in this study, both with a child aged between 7 and 8 months old, whose mothers showed depressive symptoms. These families participated in parent-infant psychotherapy lasting approximately 12 sessions. Analysis of the fathers’ participation in psychotherapy showed that their presence during sessions enables the therapy to address aspects of parenthood, and also reduce the feeling of mothers as being the only ones responsible for the family’s process of change. In regard to the technique, the presence of fathers during sessions allows the therapist to see and address the issues concerning mother-father-infant during sessions.